Adapting the Islamic Education Curriculum in the Industry 4.0 Era: Challenges and Solutions - Cut Nyak Marlina; Sari Pitri; Asraini Asraini; Anton Purnama (LaKaspia, 2026)
The Fourth Industrial Revolution has significantly transformed various aspects of education, including the development of the Islamic Education (PAI) curriculum. As digital technologies continue to evolve, the PAI curriculum is required to adapt while maintaining its role in strengthening Islamic values and character education. However, several challenges remain, including limited technology integration, insufficient learning innovation, and the inadequate incorporation of 21st-century competencies into the curriculum. This study aims to analyze curriculum innovation strategies for Islamic Education in the Industry 4.0 era. Employing a library research approach, the study examined books, journal articles, and other relevant scholarly sources, primarily published between 2020 and 2026. Data were analyzed through reduction, classification, interpretation, and synthesis techniques. The findings indicate that an adaptive and innovative Islamic Education curriculum should integrate digital literacy, critical and creative thinking skills, collaborative learning, and the strengthening of Islamic values. Such integration enables students to develop strong character, global competitiveness, and readiness to face the challenges of the digital age. The study proposes a digital-religious integrative curriculum model that combines technological competence, digital literacy, and Islamic moral values to support sustainable educational development in the modern era.